Integration of Social Context vs. Linguistic Reference During Situated Language Processing - Maquate, Katja; Knoeferle, Pia (Frontiers in Psychology, 2021)
Findings on language comprehension suggest that many kinds of non-linguistic cues can rapidly affect language processing. Extant processing accounts of situated language comprehension model these rapid effects and are only beginning to accommodate the role of other, emotional cues. To begin to establish a detailed characterization of distinct cues and their relative effects, three visual-world eye-tracking experiments assessed the relative importance of two cue types (action depictions vs. emotional facial expressions) as well as the effects of the degree of naturalness of social (facial) cues (smileys vs. natural faces). We predicted to replicate previously-reported rapid effects of referentially-mediated actions. In addition, we assessed distinct world-language relations. If how a cue is conveyed matters for its effect, then a verb referencing an action depiction should elicit a stronger immediate effect on visual attention and language comprehension than a speaker’s emotional facial expression. The latter is mediated non-referentially via the emotional connotations of an adjective. The results replicated a pronounced facilitatory effect of action depiction (relative to no action depiction). By contrast, the facilitatory effect of a preceding speaker’s emotional face was less pronounced. How the facial emotion was rendered mattered in that the emotional face effect was present with natural faces (Experiment 2) but not with smileys (Experiment 1). Experiment 3 suggests that contrast, i.e., strongly opposing emotional valence information vs. non-opposing valence information might matter for the directionality of this effect. These results are the first step towards a more principled account of how distinct visual (social) cues modulate language processing, whereby visual cues that are referenced by language (the depicted action), co-present (the depicted action), and more natural (the natural emotional prime face) tend to exert more pronounced effects.